2020
DOI: 10.1007/s12028-020-00993-5
|View full text |Cite
|
Sign up to set email alerts
|

Catastrophic Intracranial Hemorrhage in Two Critically Ill Patients with COVID-19

Abstract: Although the most common symptoms of COVID-19 are cough, fever, and anorexia, neurologic manifestations and complications have been observed, particularly among critically ill patients; these include headache, dizziness, encephalopathy, taste and smell impairment, seizures, and stroke [1,2]. Here, we present two cases of patients with COVID-19 who developed catastrophic intracranial hemorrhage and cerebral edema.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 7 publications
(14 reference statements)
0
36
0
Order By: Relevance
“…The remaining 80 articles (275 patients), which satisfied the abovementioned criteria, were included in this review. We found 226 cases of patients who developed IS during COVID-19 infection ( 16 , 18 , 20 , 22 29 , 63 106 ), 35 cases of intracranial bleeding ( 25 , 72 , 74 , 100 104 ), and 14 cases of CVST ( 22 , 31 , 105 113 ). Individual case descriptions are available in the Supplementary Material (S1 , S2 , S3) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The remaining 80 articles (275 patients), which satisfied the abovementioned criteria, were included in this review. We found 226 cases of patients who developed IS during COVID-19 infection ( 16 , 18 , 20 , 22 29 , 63 106 ), 35 cases of intracranial bleeding ( 25 , 72 , 74 , 100 104 ), and 14 cases of CVST ( 22 , 31 , 105 113 ). Individual case descriptions are available in the Supplementary Material (S1 , S2 , S3) .…”
Section: Resultsmentioning
confidence: 99%
“…Acute intracranial bleeding was reported in 35 patients with COVID-19 in the literature ( Table 2, Supplementary Table 2): 24 patients (68.57%) had intracerebral hemorrhage (ICH), 4 patients (11.43%) had non-traumatic subarachnoid hemorrhage (SAH), and the remaining 7 patients (20%) had the simultaneous presence of SAH and ICH. The mean age of the 35 patients with intracranial bleedings was 59.89 ± 11.91 years and 67.4% were males (16,25,28,64,71,73,(107)(108)(109)(110)(111)(112)(113)(114)(115)(116)(117)(118)(119)(120)(121). Two of the 11 patients with non-traumatic SAH (regardless of the presence of ICH) were found to have a ruptured dissecting aneurysm (one in the posterior inferior cerebellar artery; one in the pericallosal artery).…”
Section: Intracranial Bleedingmentioning
confidence: 99%
“…19 Articles [39], [57], [58], [60], [63], [75] [86]), [92], [98], [99], [100], [101], [106], [107], [108], [109], [110], [111], [112 [101], [102], [114], [115], [116], [117], [118], [192] Dixon L et al [149] reported ANE in a 59 Y/O F with history of aplastic anemia who died despite steroid therapy.…”
mentioning
confidence: 99%
“…So far, only case reports of devastating intracerebral hemorrhages have been published. (10,11) We can only speculate why the rate of intracerebral hemorrhages is so high in the ARDS collective. For SARS-CoV2, neuroinvasion and neurotropism have been reported and the Coronavirus was isolated from cerebrospinal uid and brain tissue.…”
Section: Intracerebral Hemorrhages and Ardsmentioning
confidence: 99%
“…(9) By now, three cases have been reported with massive intracerebral hemorrhage. (10,11) During the treatment of our cohort of critical ill COVID-19 patients, three fatal intracerebral hemorrhages occurred. We therefore raised the question if intracerebral hemorrhage is more common in critically ill COVID-19 patients with respiratory failure compared to the general population of patients with acute respiratory distress syndrome (ARDS).…”
Section: Introductionmentioning
confidence: 97%